Menumbuhkan Kesadaran dan Partisipasi Mahasiswa dalam Pengolahan Sampah Botol Plastik: Studi Kasus di UIN Syarif Hidayatullah - Oktapiani, Rahma Amelia (Jurnal Ekologi, Masyarakat dan Sains, 2025)
Environmental problems especially related to plastic waste are still unresolved issues. This is due to the lack of individual awareness and effective waste management. This study uses a descriptive quantitative approach to analyze students' interest in processing plastic bottle waste in everyday life. A survey via Google Form was conducted on 120 students from 12 departments divided into three categories of study fields. The results showed that 100% of respondents were aware of the seriousness of the plastic bottle waste problem; in addition, 91% of students were interested in processing plastic bottle waste, but they felt that there were no facilities or activities that supported the development of this interest.